The development of geothermal energy as a renewable power plant - Putri, Dennya Angeline Ardiyanto; Sulhan, Muhammad (Journal of Earth Energy Engineering, 2023)
Geothermal energy is a sustainable and ecologically beneficial energy source, it is believed that Indonesia alone has 40% of the world's geothermal energy reserves of roughly 28.000 MW. The Indonesian government expects the geothermal power plant installed capacity to reach 10.000 MW by 2025. However, the installed capacity remained at 1.739 MW until 2014. Aside from that, the Indonesian government has made significant investments to expand the geothermal sector through different current rules. This research aims to determine the absorption of geothermal energy as an alternative to power generation and many elements of the associated hurdles, such as natural and human resources. In addition, this paper also creates new model parameters that significantly improve model performance. Analysis of system dynamics methods and modelling and simulation methods are used for fast and accurate results. According to a literature analysis done by collecting secondary data from journals and associated research publications, existing conditions are judged insufficient to meet the installed capacity of geothermal energy with a target of 3.458 MW in 2025 based on simulation results of forecasts through 2050. Factors impeding progress include the government's lack of coordination and implementation difficulties. Furthermore, because the financial sector was redirected to cope with the economic crisis, the pandemic scenario in 2020 was one of the impediments. Based on these criteria, the optimum solution was sought by expanding installed electricity capacity and raising the selling price of geothermal power with a target of 24.5% and electricity output of 13.263 GWh.